Prevalence of chronic traumatic encephalopathy in athletes with repetitive head impacts: A systematic review and meta-analysis - Qi, B.; Tan, J.; Feng, D.; Guan, L.; Li, J.; Cao, M.; Zou, Y. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Chronic traumatic encephalopathy (CTE) is a neurodegenerative disorder associated with repetitive head impacts (RHI), which is commonly observed in athletes participating in contact sports. This systematic review and meta-analysis aimed to provide a clearer elucidation of the prevalence, risk factors, and potential outcomes of CTE in athletes. Through a comprehensive search of PubMed, EMBASE, Web of Science, and Google Scholar (January 2015 to July 2024), we ultimately included eight eligible studies with a low risk of bias involving 1000 former contact sports athletes diagnosed by neuropathological methods. Data were analyzed in a random-effects meta-analysis. The results indicated that the pooled prevalence of CTE in contact sport athletes was 53.7% (95% CI: 37.6-69.5, I2 = 93.7%). Subgroup analyses revealed that rugby players exhibited the highest prevalence at 64.7% (95% CI: 48.5-79.5, I2 = 0%), followed by American football players at 53.0% (95% CI: 33.2-72.4, I2 = 92.9%). By participation level, the prevalence was estimated at 44.1% (95% CI: 29.6-59.1, I2 = 84.5%) in amateur athletes and 72.8% (95% CI: 50.9-90.5, I2 = 91.6%) in elite athletes. Notably, the suicide rate among individuals diagnosed with CTE was 39.0% (95% CI: 12.7-69.0, I2 = 94.4%), and the pooled prevalence of CTE in non-suicidal athletes was 30.1% (95% CI: 6.9-60.4, I2 = 97.8%). These findings reveal the high prevalence of CTE in contact sport athletes exposed to RHI, especially at elite-level competition, and emphasize suicide as a potential outcome. Further studies should incorporate more female athletes to comprehensively assess the risk factors, outcomes, and effective prevention strategies for CTE.